Pendampingan Keagamaan Majelis Taklim Mifthaul Ulum Desa Sulai Kecamatan Ulumanda - Sappeami; Ridwan; Baharuddin; Fitri, S; Asmuna; Hasriati; Jirana; Sarkia; Riskawati; Muh. Yasir; Reski Febriani; Muslim (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2026)
Based on the results of a preliminary observation, the activities of Majelis Taklim Miftahul Ulum in Sulai Village, which were previously conducted once a month, have not been active in recent months. This community engagement program aimed to enhance participants’ understanding through practical mentoring on the procedures of thaharah (ritual purification), as well as to foster religious awareness and spiritual responsibility among the women members of the majelis taklim regarding the importance of maintaining both physical and spiritual purity as the fundamental foundation of worship. This mentoring activity employed the Participatory Action Research (PAR) method, which integrates research, action, and direct community participation in a cyclical process to address problems and empower the community. The implementation of this community service program adopted participatory and educational approaches. The results indicated that, prior to the mentoring program, the level of understanding among the women members of Majelis Taklim Miftahul Ulum in Sulai Village regarding the concept and procedures of thaharah was relatively low. The implementation of the mentoring program had a positive impact on improving the quality of their religious practices. This impact was evident not only in the technical aspects of worship performance but also in changes in attitudes, increased spiritual awareness, and the strengthening of women’s roles in fostering religious life within their families.